Case Studies in Topological Design and Optimization of Additively Manufactured Cable-nets. (April 2019) - Tish, Daniel; McGee, Wes; Schork, Tim; Thün, Geoffrey; Velikov, Kathy
Abstract: Advances in additive manufacturing technologies have availed new modes of design and production across the design and engineering disciplines. While lightweight cable-net structures have long captured the imagination of engineers and architects, there has so far been little research on the opportunities afforded by large-scale additive manufacturing of cable-net structures for form-active or performative tensile surfaces. Additive manufacturing opens up the possibility of manufacturing tensile surfaces beyond knitted, woven nets, or mechanically fastened nets, and expands the types of materials that can be used in such systems. This paper discusses research in novel approaches to the topological design and optimization of cable-nets enabled by the additive manufacturing of elastomeric materials. Through three realized case studies, the topological structure is used to determine the formal, behavioral, and performance-based properties of the cable-net system. This is achieved through the reorientation of a standard quad-grid topology, through a material programming method that embeds non-natural three-dimensional forms into two-dimensional patterns, and through a new meso-scale density-based topological optimization method.